AB0199 Anti-tnf monoclonal antibody used for scintigraphic visualisation of synovitis in ra. (1st June 2001) - Barrera, P; Oyen, WJ; Boerman, OC; Van de Putte, LB; Corstens, FH; Van Riel, PL
Abstract : Background: Tumour necrosis factor α (TNFα) is a crucial proinflammatory cytokine present in inflamed joints of rheumatoid arthritis (RA) patients. Therapies using anti-TNFα monoclonal antibodies (MAb) have proven their efficacy in RA and other chronic inflammatory diseases. Such antibodies could also be used to detect inflammation. Objectives: To determine the potential of a 99 Tc-labelled anti-TNFα MAb to image synovitis in patients with RA. Methods: Eight consenting patients with active RA, defined as a disease activity score (DAS) > 3.2 were enrolled in the study. No previous anti-TNFα therapy was allowed. NSAIDs and low-dose steroids were kept stable during the study. Patients received a single dose of 300 MBq 99 Tc-labelled anti-TNFα MAb and whole body images and spot views were obtained with a double-headed gamma camera. Results: Prominent uptake of the radiolabeled anti-TNFα MAb was clearly visible in inflamed joints of all patients examined. The distribution of the label was compatible with binding to both soluble and membrane-bound TNFα. To elucidate the latter, displacement studies are now in process. Conclusion: Our results show that scintigraphic detection of inflammation with anti-TNFα MAb is feasible. The potential use of this technique to monitor disease activity and response to therapy deserves further investigation.